Oxidative stress mediated neurodegeneration; A cellular perspective - Noushad , Shamoon; Sajid, Ujala; Ahmed , Sadaf; Saleem, Yusra (International Journal of Endorsing Health Science Research, 2019)
Background: Environmental toxins, nutritional discrepancies, genetic predispositions, and lifestyle modifications induce a variety of stresses on the human brain and body. Such chronic stressors can influence the onset and progression of neurodegeneration via cellular alterations. In this systematic review, we have discussed the role of oxidative stress in causing neurodegeneration. Moreover, the chemical, metallic and other etiological factors that stimulate oxidative stress and results in the development of neurodegenerative disorders are also explored and summarized. Methodology: A systematic review was conducted to investigate the impact of oxidative stress on the human brain in relation to neurodegeneration. The human studies focusing on neurobiology and cellular changes in brain, investigating the pathway of oxidative stress leading to neurodegeneration through mitochondrial dysfunction and cellular alterations, published during 1st January 2000 to 31st March 2019 were identified and included in this systematic review. Result: Following the PRISMA guidelines, 13 out of 1169 studies met the eligibility criteria and were included in the quantitative synthesis and screening. These studies focused on the features like cellular factors, metal exposure, and aging, inducing oxidative stress-related neurodegeneration. 6 studies described mitochondrial alterations resulting in oxidative stress due to an increase in the production of reactive oxygen species (ROS), oxidation of proteins, peroxidation of lipid and damages to the deoxyribonucleic acid (DNA) and ribonucleic acid (RNA). While the data from 5 studies suggested the loss of mitochondrial activity in response to metal exposure. 2 experimental studies specified the effect of aging and self-implication of oxidative stress in the brain. Conclusion: Although there are sufficient evidence that supported the hypothesis that stress is significantly associated with neurodegeneration but it is still not considered as a primary instigator in neurodegenerative disorders. However, it can be concluded on the basis of this review that it has been involved in the propagation of cellular alterations and mitochondrial dysfunction that further leads to neurodegeneration.